ANALYSIS OF FACTORS CAUSED BY PATIENT COMPLAINTS AT PUYUNG HEALTH CENTER - Fitriana, Huniza; Menap, Menap; Khaliq, Abdul (Jurnal Ilmu Kesehatan Masyarakat, 2024)
One of the issues that health facilities, including community health centers, had to address was patient complaints. Therefore, the aim of this research was to analyze the factors that caused patients to complain at the Puyung Health Center. To identify these causal factors, several hypothetical variables were used, such as patient perceptions, facilities and infrastructure, service procedures, officer competency, and officer discipline. The research design employed was analytical-observational, using a cross-sectional approach. The sample in the study consisted of 94 patients. The instrument in this research was a questionnaire for each variable. The data were then analyzed using bivariate analysis (crosstab) to determine the relationship between the independent and dependent variables and a multivariate logistic regression test to identify the independent variables that caused patient complaints. The results of the research revealed that there was an individually significant relationship between patient complaints and patient perceptions, facilities and infrastructure, service procedures, officer competence, and officer discipline. In addition, information was obtained that service procedures were the dominant factor that significantly caused patient complaints at the Puyung Community Health Center.